2020
DOI: 10.1007/s10815-020-01864-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal physical activity and sedentary behaviour before and during in vitro fertilization treatment: a longitudinal study exploring the associations with controlled ovarian stimulation and pregnancy outcomes

Abstract: Purpose To evaluate the association of objectively measured physical activity (PA) and sedentary behaviour before and during in vitro fertilization (IVF) with controlled ovarian stimulation (COS) and pregnancy outcomes. Methods This longitudinal study involved 107 infertile women undergoing IVF treatment. PA and sedentary behaviour were measured for 14 consecutive days using accelerometry as follows: (1) before IVF treatment, (2) during IVF at the implantation time, immediately after embryo transfer, and (3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…Our findings do not support either an association of the separate physical and sedentary activity levels of the woman and man with the chance to get pregnant and to have a baby. This is in line with previous findings, where no associations of objectively measured physical and sedentary activities in women before and during IVF treatment with IVF outcomes such as implantation, clinical pregnancy and live birth were detected [ 21 , 37 ]. Additionally, a recent preconception prospective cohort study on 785 women with a previous history of a pregnancy loss analyzed self-reported PA and did not detect any effect of PA on the clinical pregnancy loss [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings do not support either an association of the separate physical and sedentary activity levels of the woman and man with the chance to get pregnant and to have a baby. This is in line with previous findings, where no associations of objectively measured physical and sedentary activities in women before and during IVF treatment with IVF outcomes such as implantation, clinical pregnancy and live birth were detected [ 21 , 37 ]. Additionally, a recent preconception prospective cohort study on 785 women with a previous history of a pregnancy loss analyzed self-reported PA and did not detect any effect of PA on the clinical pregnancy loss [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although this is an observational study and causality need to be demonstrated in future randomized controlled trials, our findings support the notion that PA could positively interfere with couples’ general reproductive health. Additionally, previous studies are suggesting that PA may have beneficial effect on general reproductive health rather than on a specific ART treatment outcomes, like embryo implantation and pregnancy rate [ 21 , 37 ]. Evenson et al detected beneficial effect of PA in women who were active in the year preceding infertility treatment having more likely favorable pregnancy outcome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations